Estimation of Adropin and its correlation with glycemic indices in patients with type 2 diabetic mellitus - Abed, Sahar Saad; AL-Shammaree, Shatha Abdul Wadood (Iraqi Journal of Science, 2025)
Adropin is a newly identified protein involved in the regulation of energy balance and carbohydrate metabolism; it has also been implicated in the development of insulin resistance. Despite the fact that it may offer a potential link to T2DM, conflicting reports exist in the literature with respect to the association between adropin and T2DM; further investigation was thus conducted. The aim of this study is to assess the association between serum Adropin levels and glycemic indices in patients with T2DM. This study included 100 participants; fifty of them had T2DM without any complications, compared with 50 apparently healthy subjects representing control group. The age range for the T2DM patients was 18-75 years, while the control group ranged from 22-58 years, with an equal distribution of sexes in both groups. Adropin and fasting insulin hormone were measured by ELISA kits. Glycated hemoglobin (HbA1c) Fasting Blood Sugar (FBS) levels were also measured while Insulin resistance (IR) and glycemic indices were calculated. The concentrations of Adropin were higher with significance (P<0.05) in T2DM group when compared with control group and a positive correlation was found between Adropin and insulin levels in both groups. The Receiver Operating Characteristic analysis (ROC) showed that Adropin can predict T2DM when its level >1250.7 pg/ml with AUC=97.9%, sensitivity of 100% and specificity of 96.1%. Measurement of glycemic indices include (Insulin, HOMA-IR, S%, B%, G/I ratio, QUICKI, McAuley, and TyG index) revealed that IR and TyG index were higher in T2DM while B%, S%, QUICKI index, and McAuley index were lower in T2DM. Adropin is connected to T2DM and may be used as prognostic marker for T2DM. Further studies with larger sample sizes are recommended confirm these results.